PENGEMBANGAN UNIT KEGIATAN BELAJAR MANDIRI (UKBM) KIMIA BERBASIS DISCOVERYLEARNING PADA MATERI REAKSI REDOKS KELAS X MIA SMA NEGERI 1 MAUMERE - Sri Sulystyaningsih N. D.Tiring (Yayasan Akrab Pekanbaru, 2019)
This study aims to find out 1) the stages of developing chemistry based discoverylearning-based UKBM, 2) the feasibility of discoverylearning-based chemical UKBM. This study uses the Borg & Gall procedure with nine stages: 1) the research and information gathering stage, 2) the planning stage, 3) the development of the product draft, 4) the initial field trials, 5) revising the results of the trials, 6) the main field trials , 7) revising the product of field test results, 8) field implementation test, 9) refinement of the final product. Initial field trials with subjects six students and one teacher, main field trials with subjects 30 students and one teacher and field implementation trials with subjects 60 students and two teachers. The trial was conducted at Maumere 1 High School. The feasibility of UKBM is obtained from the validator assessment through the UKBM validation sheet using the Aiken Vormula and the responses of teachers and students through a questionnaire using a Likert scale. Data collection techniques through interviews, documentation and questionnaires. The results showed: (1) the stages of developing chemistry based learninglearning based UKBM, namely chemistry UKBM that has been validated and revised based on the advice of the validators and has been tested to prospective users, (2) the feasibility of chemistry based discoverylearning based on the validators obtained Value Aiken â‰¥ 0.87 which shows that UKBM is appropriate to be used, and the average questionnaire responses of students and teachers in all tests were obtained in the '' Good '' category. Small-scale trials obtained scores from students 66.5 and 118 teachers. Medium-scale trials obtained scores from students 62.1 and teachers 118. Large-scale trials obtained grades from students 63.8 and teachers 116.5.